Literature Review: Efektivitas Interprofessional Education (IPE) Terhadap Peningkatan Kemampuan dan Kompetensi antar Profesi Kesehatan - Morato, Amaze Grace Davidz; Diarthini, Ni Luh Putu Eka; Utami, Desak Ketut Indrasari (Politeknik Kesehatan Tanjung Karang, 2021)
Interprofessional Education (IPE) is a learning process between students from various health workers from different educational backgrounds, that interacting and collaborating to produce and provide promotive, preventive, curative, and rehabilitative health services. The implementation of the IPE program in academic education is important to help develop the concept of collaboration between health professionals to prepare and create better, professional, and competent health workers to deal with health problems. The purpose of this study was to determine how the effectiveness of interprofessional education in increasing the ability and competence of health professionals.Â The method in this study is a literature study article or narrative review in the form of a study of several research journals related to the effectiveness of interprofessional education on increasing abilities and competition between health professions obtained through Google Scholar, PubMed, and Science Direct. The benefits of IPE activities are students can learn to collaborate and function in a team and bring this knowledge, skills, and attitudes into future practice through enhancing several aspects such as communicating, collaborating, determining the roles and responsibilities of each profession, conflict management, decision making, sharing knowledge and skills and finally mutual respect between friends. Based on the cited literature review, it can be cited that interprofessional education (IPE) is a way to increase competence and collaboration skills between professions so that it can create health professionals who are professional, capable, and able to improve the quality of health services.